How Does Aviation Contribute to the Regenerative Tourism Framework? - Wu, Hanjun; Cui, Claire; Tsui, Kan (Elsevier, 2026)
This research note explores whether aviation can serve as a regenerative partner in a small regional tourism system. Based on Analytic Hierarchy Process (AHP) findings and three executive interviews conducted in Marlborough, New Zealand, the study demonstrates that stakeholders prioritise cultural vitality, social connection, and community well-being over purely economic outcomes. The interview evidence also suggests that aviation influences more than just access and connectivity. It affects participation, mobility, and the distribution of tourism benefits in everyday regional life. Simultaneously, the findings highlight an important tension: airfare affordability and aviation infrastructure are not, in themselves, regarded as regenerative outcomes, yet they are necessary conditions for realising the broader social and cultural benefits. This potential is further limited by fragmented priorities among aviation, tourism, and public-sector actors. The note contributes by explicitly integrating aviation into the regenerative tourism literature and demonstrating that its value extends beyond access and connectivity to include the place-based benefits it can help foster.
Keywords: 1504 Commercial Services; 1506 Tourism; 3504 Commercial services; 3508 Tourism; Regenerative tourism framework; Air transport; Social; Economic; Environment; Cultural; Smaller regions